The Influence of Service Quality and Price Perception on Purchase Decisions At HBG Car Workshops in Pekanbaru - Quraysh; Harifuddin; Sudianto (International Journal of Business and Quality Research, 2023)
Automotive development in Indonesia from year to year has experienced rapid progress, one of which is cars. In purchasing decisions, there are several influencing factors, one of which is the quality of service, the quality of service is very decisive for a consumer in making a purchase. If the quality of service is poor, then the price offered, no matter how low, consumers will switch to another place. The data analysis technique used in this study is using the formula validity test, reliability test, classic assumption test, normality test, multiconearity test, heteroscedasticity test, multiple linear regression analysis, t test, F test and the coefficient of determination. The results of the study concluded that service quality has a significant effect on purchasing decisions at the HBG Car Repair Shop in Pekanbaru. Price perception has a significant effect on purchasing decisions at the HBG Car Repair Shop in Pekanbaru. Service quality and price perceptions influence purchasing decisions at the HBG Car Repair Shop in Pekanbaru. Variation in purchasing decisions 66.0% can be explained by service quality and price perceptions, the remaining 34.0% is explained by other variables not examined in this study.